Plastic-Free Coastlines : A Contribution from the Maghreb to Address Marine Plastic Pollution - World Bank (Washington, DC, 2022)
Marine plastic pollution is threatening the potential of the blue economy in the Middle East and North Africa (MENA) region. Recognizing the urgent need to address this problem, the governments of Morocco and Tunisia decided to partner with the World Bank to address marine plastic pollution by taking circular economy approaches. Reducing marine plastic pollution makes socioeconomic sense. This report summarizes the experiences of Morocco and Tunisia to address marine plastic pollution and liberate their coastlines from plastics (Littoral Sans Plastique (LISP)) with the first phase of technical assistance by the Bank.